THE DEFENSIBLE SPACE CONCEPT IN NEIGHBOURHOOD PARK CASE STUDY: TAMAN TASIK PUCHONG PERDANA, SELANGOR, MALAYSIA - Marzukhi, Marlyana Azyyati; Afiq, Mohd Aizzat; Ling Hoon Leh, Oliver; Abdullah, Yusfida Ayu (PLANNING MALAYSIA, 2018)
Open space can contribute to the overall wellbeing of life by providing social and recreational focal points. However, open space may also be associated with undesirable qualities of a place such as crime activities that affect negatively its quality and the surrounding. Thus, to create a safe and comfort open space area, the defensible space concept is seen as an important approach to deter crime from occurring and to sustain the safety environment. Therefore, this research objective is to investigate whether the elements of the defensible space concept; territoriality, surveillance, and image, may be used in the planning of neighbourhood park. A study was carried out at Taman Tasik Puchong Perdana, Selangor by using a questionnaire survey to collect information from the visitors. The findings show that the defensible space concept with all the three elements was not implemented, which further may lead to the crime activities in the neighborhood park.